Integrated Application for Worship Scheduling and Church Finance Based on Android and Web - Devani Maria Naulu; Anna Dina Kalifia (bit-Tech, 2025)
The development of information technology has driven digital transformation in the management of church administration, including service scheduling, financial reporting, and congregational services. However, most existing systems are still single-platform and do not support real-time data synchronization, resulting in limitations in efficiency and transparency. This research aims to design and implement an integrated application based on Android and Web that is able to manage worship scheduling, seat reservations, and church financial administration synchronously and transparently. The development method used is the Waterfall model, which includes the stages of needs analysis, design, implementation, testing, and maintenance. The system was developed using the Flutter framework with the Dart programming language and Firebase Firestore (NoSQL) as a database that supports real-time data synchronization between platforms. The test is carried out using the Black Box Testing method to assess the functional suitability of the system to the needs of the user. The results of the implementation show that all the main features of worship scheduling, recording financial transactions, and congregational seat reservations work well on both platforms. Real-time data synchronization runs steadily without lag, and the user interface proves to be accessible and responsive. This integrated application has succeeded in improving the efficiency of church administration, transparency of financial management, and the convenience of congregations in participating in worship activities. Thus, this system can be a model for the digitalization of the modern church oriented towards the openness, mobility, and accountability of religious organizations.